Revolusi mental dalam cerita Babad Alas Wanamarta - Wardhani, Novia Wahyu; Noorrochmat, N (Jurnal Civics: Media Kajian Kewarganegaraan, 2016)
The purposes of this study were to describe the stories of Wanamarta Chronicle in Wayang Orang Sekar Budaya at TVRI, describe the mental revolution embedded in Wanamarta Chronicle, and to explain the relevance of the values in the Chronical story in Wanamarta to values that exist now. The method used was qualitative with hermeneutic approach. The result were 1) Wanamarta chronicle tells the Pandawa transform the jungle forest into a state territory, 2) mental revolution embedded on Wanamarta chronicle is reflected with the new soul of Pandawa from five "jin". Its relevance are optimistic, resilience, and never give up which can be transformed as underlying values of mental revolution policy in Indonesia.